The decay of ¹⁹¹Pt - Lashko, A.P. (Вопросы атомной науки и техники, 2009)
The energy difference for γ268 and γ295 lines was measured with gamma-spectrometer. The γ268 keV transition is excited in the ¹⁹¹Pt decay, while another transition, the energy of which is known up to a high precision, accompanies the ¹⁹²Ir decay. A measured energy value of the 3/2- → 7/2- transitions (268 keV ), along with the data from our previous work, allowed us to perform a high-precision calculation of energy levels in ¹⁹¹Ir and energies of γ-rays deexciting these levels. На гамма-спектрометрі поміряли різницю енергій ліній γ268 та γ295 кеВ. Перехід γ268 кеВ збуджується при розпаді ¹⁹¹Pt, а другий, енергія якого відома з високою точністю, супроводжує розпад ¹⁹²Ir. Отримане значення енергії переходу 3/2- → 7/2- 268 кеВ дозволило, разом з даними нашої попередньої роботи, розрахувати з високою точністю енергії рівнів ¹⁹¹Ir та енергії розряджаючих їх γ-променів. На γ-спектрометре измерена разность энергий линий γ268 и γ295 кэВ. Переход γ268 кэВ возбуждается при распаде ¹⁹¹Pt, а второй, энергия которого известна с высокой точностью, сопровождает распад ¹⁹²Ir. Измеренное значение энергии перехода 3/2- → 7/2- 268 кэВ позволило, совместно с данными нашей предыдущей работы, рассчитать с высокой точностью энергии уровней ¹⁹¹Ir и энергии разряжающих их γ-лучей.